Adsorption of surfactants on resin-asphaltene associates in oil disperse systems - Yakavets, Natallia V.; Krut’ko, Nikolai P.; Luksha, Olga V.; Kouznetsova, Tatyana F. (Journal of the Belarusian State University. Chemistry, 2024)
As a result of physical and chemical studies using the methods of IR spectroscopy, X-ray fluorescence spectrometry, thin layer chromatography and elemental analysis, the composition and structure of resin-asphaltene substances were studied. By the method of low-temperature adsorption – desorption of nitrogen, the influence of surfactants of cationic and non-ionic nature on the textural properties of resin-asphaltene associates was determined, their specific surface area, energy constant CBET, volume and average pore diameter were estimated. It has been established that the measured isotherms of low-temperature adsorption – desorption of nitrogen by samples of modified resin-asphaltene substances are a complex combination of physical sorption isotherms of types V and IV, inherent in macromesoporous materials. For resin-asphaltene substances, a decrease in the specific surface area, pore volume and energy constant CBET is observed, which indicates an increase in the hydrophobicity of their surface due to adsorption interaction with the surfactant. It was revealed that the greatest modifying effect is manifested in the presence of the non-ionic surfactant ethylenediamine tetrabis(ethoxylate-block-propoxylate)tetrol. The results of low-temperature adsorption – desorption of nitrogen correlate with the data obtained by studying of the capillary properties of the surface of resin-asphaltene substances when they are wetted with n-hexane.